Editorial (Jonathan Edwards studies, 2020)
This spring 2020 issue of Jonathan Edwards Studies appears amidst pandemic, when many institutions, states, even countries are entirely shut down, or nearly so, awaiting what will come next. We mourn to hear of so many lives affected and lost but also rejoice to see people selflessly working and caring for each other. Amidst it all, we see the truth in the old saying, Life is short, but art is long. And the task and privilege of scholarship goes on.